2022
DOI: 10.3389/fpls.2022.826473
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Heat Stress in Plant Male Reproduction

Abstract: In flowering plants, male reproductive development is highly susceptible to heat stress. In this mini-review, we summarized different anomalies in tapetum, microspores, and pollen grains during anther development under heat stress. We then discussed how epigenetic control, particularly DNA methylation, is employed to cope with heat stress in male reproduction. Further understanding of epigenetic mechanisms by which plants manage heat stress during male reproduction will provide new genetic engineering and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…High temperatures are known to modify DNA methylation patterns and plant development (Naydenov et al 2015; Chen et al 2016; Kawakatsu et al 2016; Malik 2022). Data from the 1001 epigenomes project (Kawakatsu et al 2016) revealed that the TAM promotor contains very few DNA methylation marks in leaf material of most accessions at control temperature conditions (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…High temperatures are known to modify DNA methylation patterns and plant development (Naydenov et al 2015; Chen et al 2016; Kawakatsu et al 2016; Malik 2022). Data from the 1001 epigenomes project (Kawakatsu et al 2016) revealed that the TAM promotor contains very few DNA methylation marks in leaf material of most accessions at control temperature conditions (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is an essential epigenetic mechanism for plants at the reproductive stage during HT stress (Malik and Zhao, 2022). Until now in plants, four distinct types of DNA methyltransferases are known, namely (i) MET1 (DNA-methytransferase1), (ii) CMT (chromomethyltransferase), (iii) Dnmt2 (DNA-methyltransferase2) and (iv) DRM (domain rearranged methyltransferase) and four distinct demethylases for catalysing cytosine methylation including (i) DME (Demeter), (ii) DML2 (Demeter like 2), (iii) DML3 (Demeter like 3) and ROS1 (repressor of silencing 1) were found (Malik and Zhao, 2022). During HT stress, various genes are involved in DNA methylation.…”
Section: Epigenetics Involved In Male Sterility During Ht Stressmentioning
confidence: 99%
“…In plants, DNA methylation can be established through the RNA-directed DNA methylation (RdDM) pathway and it requires 24 nucleotide siRNAs (Singh and Prasad, 2022b). In anthers, CHH methylation caused by RdDM is more prominent as compared to CH and CHG methylation and RdDM function is reduced in the initial stages (TS and TDS) of growth as compared to late stages (anther dehiscence stage) during HT stress condition (Ma et al, 2018;Malik and Zhao, 2022). In further studies, during HT stress, Naydenov et al (2015) found the up-regulation of Pol IV and Pol V large subunits, Methylase 1 (MET1), domain rearranged methyltransferase 2 (DRM2) and chromomethlyase 3 (CMT3).…”
Section: Epigenetics Involved In Male Sterility During Ht Stressmentioning
confidence: 99%
“…The histone proteins H1, H2A, H2B and H3 with the exception of H4 have specialized histone variants that reprogram the gene expression responsible for heat acclimation and heat stress memory. Several key genes and networks regulating the heat response have been identified, and heat stress memory is associated with epigenetic changes ( Li et al., 2021 ; Malik and Zhao, 2022 ). In contrast to hormonal regulation underlying heat stress at the transcriptional level, epigenetic regulation under stress in plants remains elusive, suggesting that identifying key mechanisms is important.…”
Section: Regulation Of Heat Stress In Plantsmentioning
confidence: 99%